PENGARUH LINGKUNGAN KERJA, GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA RESTORAN TANATAP - Muhammad Rizky Yoga; Verry Cyasmoro (LPPM Universitas Asa Indonesia, 2025)
This study aims to analyze the influence of the work environment, leadership style and disturbances on all employees of Tanatap Restaurant. This study used a questionnaire with a purposive sampling method. Based on the results of research and data analysis conducted on 103 employees of Tanatap Restaurant, it can be concluded that the Work Environment has a significant partial effect on employee performance. A safe, comfortable, and supportive work environment both physically and psychologically can increase employee productivity and performance. This is proven through a t-test which shows a significance value <0.05. However, Leadership Style does not have a significant partial effect on employee performance.